LIMITATIONS ON THE POSSIBILITY TO SETOFF IN LIQUIDATION PROCEEDINGS IN THE HUNGARIAN LAW - Máté, Mohai (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
After the starting date of the liquidation, there is only a place for setoff in case of special conditions included in the Hungarian Bankruptcy Act. Therefore, if the debtor is in liquidation, the rules of the Civil Code concerning setoff can only be applied with the exceptions set out in the Bankruptcy Act. In the following, we examine the provisions that can be linked to setoff in the Bankruptcy Act or that have some effect on the possibility of setoff. To give a transparent picture of the relevant provisions, we cite the rules of the Act.